142k views
14 votes
What is the simplified expression for 14z-3-(6-5z)

User Phocs
by
4.5k points

2 Answers

3 votes

Answer:

19z - 9

Explanation:

14z - 3 -(6 - 5z)

= 14z -3 - 6 + 5z

= 19z - 9

Hope this helps

User CRGreen
by
5.0k points
4 votes

Given :

  • 14z - 3 - (6-5z)

To Find :

  • The simplified expression.

Answer :

The given expression to us is ,

⇒14z - 3 - (6-5z)

Open the brackets ,

⇒ 14z - 3 - 6 +5z

Group like terms and constants ,

⇒ (14z + 5z ) + (-3-6)

Simplify ,

19z - 9

Hence the required answer is 19z - 9.

I hope this helps .

User Arjun Kava
by
5.2k points